2022
DOI: 10.1590/0102-672020220002e1686
|View full text |Cite
|
Sign up to set email alerts
|

The Appendicitis Inflammatory Response Score for Acute Appendicitis: Is It Important for Early Diagnosis?

Abstract: - BACKGROUND: The use of Appendicitis Inflammatory Response clinical score in patients with suspected acute appendicitis makes the diagnosis more objective and accurate. AIMS: The aim of this study was to prospectively compare two groups with suspected acute appendicitis, analyzing the number of imaging tests requested, waiting time in the emergency department, until definition of conduct, as well as the sensitivity and specificity of this diagnostic method. METHODS: This is a prospective randomized study co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…A similar study by Andersson et al used AIR diagnostic score evaluation and successfully decreased the CT use by 44% [ 21 ]. A recently performed prospective randomized study presented a sensitivity of 100% for AIR scores since there were no false-negative AA diagnoses, implying that clinical scores can minimize the number of imaging tests and waiting time for AA diagnosis, while also improving diagnostic accuracy [ 22 ]. Therefore, all patients in our study were evaluated with Alvarado and AIR scores that helped us to detect patients with probable AA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study by Andersson et al used AIR diagnostic score evaluation and successfully decreased the CT use by 44% [ 21 ]. A recently performed prospective randomized study presented a sensitivity of 100% for AIR scores since there were no false-negative AA diagnoses, implying that clinical scores can minimize the number of imaging tests and waiting time for AA diagnosis, while also improving diagnostic accuracy [ 22 ]. Therefore, all patients in our study were evaluated with Alvarado and AIR scores that helped us to detect patients with probable AA.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that a short, in-hospital surgical delay of up to 24 h is safe in uncomplicated AA and does not increase complications and/or the perforation rate in adults [ 39 ]. Moreover, a comparable study [ 22 ] found the AIR score is safe in predicting the need for surgical treatment for patients with high AIR scores without the need for imaging examination as all these patients in both groups, who initially underwent CT scanning or straightforward surgical treatment, had a histopathologically confirmed diagnosis of acute appendicitis. Based on Andersson and colleagues’ recently performed randomized control trial, 69% of patients with an intermediate AIR score could be treated without any imaging tool [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversion rate is one of the main factors used to measure laparoscopic competence 5 . The rate of conversion evaluated by many studies was related to various factors and was more associated with higher hospital costs 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of acute appendicitis is supported by the use of a variety of clinical grading systems 8 . A clinical scoring system helps improve the first evaluation.…”
Section: Discussionmentioning
confidence: 99%